PENGARUH FAKTOR-FAKTOR PERSONAL TERHADAP SKEPTISISME PROFESIONAL AUDITOR - Dessy Larimbi; Bambang Subroto; Rosidi Rosidi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2013)
The purpose of this study was to test the impact of personal factors to auditor’s professional skepticism at Non Big 4 audit firms in East Java. Personal factors which tested in this study were personality type, auditor’s sex, and audit experience. Auditor’s personality types were classified based on Myers-Briggs Type Indicator (MBTI), audit experience was measured by auditor tenure, and auditor’s professional skepticism was measured by Hurtt (2010) professional skepticism scale. Sample used in this study were auditors at Non Big 4 audit firms in East Java, which selected by easy sampling technique (convenience sampling). Questionnaire was used as research instrument. Datas in this study were analyzed by multiple regression analysis. The results of this study indicate that INFP (introvert, intuition, feeling, perceiving) and ENFJ (extrovert, intuition, feeling, judging) personality type affects auditor’s professional skepticism. This study also found that audit experience affects auditor’s professional skepticism. The more experience an auditor, the higher the professional skepticism. On the other hand, sex differences of auditors at Non Big 4 audit firms in East Java turned out to have no effect on professional skepticism.